My digital entertainment for seniors - Rich, Jason (Que, 2016)
"The full-color, step-by-step tasks -- in legible print -- walk you through learning to use today's technology for all your entertainment needs. With My Digital Entertainment for Seniors, you'll: learn all about how you can watch movies and TV, listen to music, read books, and play games on devices you already own; get acquainted with on-demand video, music, podcasts, eBooks, and magazines, audiobooks, and games; find out how you can enjoy multiple forms of digital entertainment, without spending a fortune; discover the difference between streaming and downloading content from the Internet; watch, listen to, or read what you want, when you want it, on your television set, desktop computer, notebook computer, smartphone, tablet, eBook reader, or gaming console; learn how to stay safe, and protect yourself from identity theft or online crime when surfing the Internet, shopping online, playing games, banking online, and handling other Internet-related tasks; discover easy ways to access and experience entertainment using today's technology, without getting confused or bogged down with techno-babble."--Back cover.